Climate-crop interactions in the U.S. winter wheat belt - Zhang, Lina (My University, 2025)
Climate change poses severe challenges to global food security. Wheat is one of staple food crops worldwide, and its production faces mounting pressures from rising food demand due to quick increase in world population. Furthermore, increasing exposure to climate extremes, such as heat and drought, during sensitive growth stages can cause abrupt yield shocks, threatening its production sustainability. However, the mechanisms underlying climate-crop interactions remain poorly understood despite decades of research. The U.S. Great Plains is the nation’s primary hard winter wheat belt and breadbasket. Recent rapid changes in temperature and precipitation during wheat development have significantly affected wheat production in the region. To address these issues, we investigated how drought shocks, breeding progress, and phenological shifts have collectively shaped winter wheat resilience under historical climate change in the region. By analyzing long-term surface climate data from dryland wheat-growing regions at both county- and site levels using statistical and machine-learning approaches, we showed that the unprecedented 2022-2023 drought reduced U.S. hard winter wheat production by 37% through both yield reduction and crop abandonment, driving Dust Bowl-like impacts. Random forest and game-theoretic analyses revealed that spring drought primarily drove yield reduction, whereas fall drought dominated crop abandonment. Moreover, the La Niña phase of the El Niño-Southern Oscillation (ENSO) significantly increased abandonment rates compared to El Niño, underscoring the need to jointly address yield decline and abandonment to stabilize production under climate extremes. Analyzing cultivar-specific data from 1982 to 2020, we found that compound hot-dry (HD) events during the grain filling period reduced yields by an average of 6%, whereas breeding-driven yield gains were accompanied by reduced HD resilience: newer cultivars exhibited greater yield potential but increased sensitivity to HD stress. These findings revealed a trade-off between productivity and resilience, pointing to the urgent need to reorient breeding strategies toward increasing abiotic stress tolerance. To investigate the long-term climate trend impacts on yield, we accounted for climate-driven shifts in phenology, often overlooked in previous studies, by tracking the same cultivar cultivated in the same fields across decades. We approximated this experiment using the constant check cultivar ‘Kharkof,’ cultivated for 65 years (1960-2024) across the Great Plains, and demonstrated that long-term warming advanced phenological stages and extended the reproductive window (double ridge-heading), partially offsetting the negative impacts of heat stress. Warming also reduced cold injury in high-latitude regions, contributing to yield gains. In contrast, the fixed-season assumption overestimated the negative impacts of climate trends by nearly threefold, largely because it exaggerated the negative effects of rising temperatures. Those findings highlight the critical role of phenological shifts in modulating climate impacts on crop yields and provide a more nuanced understanding on how historical climate trends have shaped crop yields. This work provides a more nuanced view of climate-crop interactions and identifies adaptation pathways, which may benefit development of climate-informed policy for improvement of wheat breeding strategy and abiotic stress management.
Keywords: Winter wheat; Yield; Abandonment; Phenology; U.S. Great Plains; Weather